EVALUASI NILAI NUTRISI SORGUM TERFERMENTASI Cellulomonas Sp DALAM PAKAN KOMPLIT TERNAK KELINCI - Sonny A.E. Moningkey; Ronny A. V. Tuturoong; Ingriet D.R. Lumenta; Stevy P Pangemanan (Jambura Journal of Animal Science, 2022)
This study aims to obtain the best ration using fermented sorghum Cellulomonas Sp in complete feed through performance parameters of rabbit production. This research was carried out in 2 stages namely; 1) Sorghum fermentation test experiment using Cellulomonas Sp with determination of the best incubation time. 2) Research on biological test of treated feed (best results of phase 1) research formulated in a complete feed mixture for rabbits. The first phase of the study used an experimental method with a completely randomized design (CRD) with 4 treatments which was repeated 5 times. Treatment of incubation time (L) at room temperature was 4 levels, namely L1 = 7 days, L2 = 14 days, L3 = 21 days and L4 = 28 days. The observed variables were protein and crude fiber content. The second phase of the study used an experimental method with a randomized block design (RAK) based on the initial body weight of rabbits. The treatment feed consisted of 5 levels which were repeated in 3 body weight groups, each experimental unit filled with 2 male rabbits so that the number of rabbits used was 30. The treatment given was the level of use of sorghum in a complete feed ration made in pellet form with the following arrangement: R0 = Ration without using sorghum; R1 = Ration using 10% fermented sorghum Cellulomonas Sp; R2 = Ration using 20% fermented sorghum Cellulomonas Sp; R3 = ration using 30% fermented sorghum Cellulomonas Sp and R4 = ration using 40% fermented sorghum Cellulomonas Sp. The observed variables were feed consumption, body weight gain and feed conversion. The results of the Phase I study showed that the average protein content incubated at 7, 14, 21 and 28 days, respectively, was 7.23%, 7.50%, 8.77% and 8.80%, while the average fiber content was crude oil is 14.46%, 12.33%, 11.22% and 10.64%. Fermentation plays an important role in the process of increasing protein and decreasing crude fiber, because in the fermentation process there are microbes that can remodel the substrate. In the second stage of the study, it was seen that the highest ration consumption was found in the R3 treatment, which was 59.70 g/head/day, as well as the highest body weight gain was found in the R3 treatment, which was 15.91 g/head/day. The R3 treatment also showed the lowest conversion value of 3.75 compared to other treatments in this study. This shows that the R3 treatment is more efficient than the other treatments. Based on the results of the study, it can be concluded that the administration of 30% fermented sorghum Cellulomonas sp in a complete feed mixture showed the best results in terms of consumption parameters, body weight gain and feed conversion